1972
DOI: 10.1111/j.1365-2494.1972.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting Milk Production From Grassland at the Hannah Institute, 1951–70

Abstract: A study of the relationship hetween some farm and grassland management factors and milk production at the Hannah Dairy Research Institute in the period 1951-70 is reported. During this period various aspects of farm management were altered, and total annual milk production was increased from 28,400 to 63,900 gal. The major factors influencing total milk production, in order of declining importance, were: the overall rate of stocking, milk yield per cow, the numher of milking cows as a percentage of all animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…This is consistent with earlier research findings (Castle et al, 1968(Castle et al, , 1972Gordon, 1973;Fales et al, 1995) in which milk production per hectare increased with increasing SR irrespective of the effect of SR on milk yield per cow. In fact, Castle et al (1972) reported that SR explained 92% of the variation in milk production per hectare. Irrespective of SR, there was no significant (P = 0.25) effect on the amount of milk produced per kilogram of feed consumed (0.9 kg of milk/kg of pasture + silage consumed).…”
Section: Milk Production Bw and Bcssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with earlier research findings (Castle et al, 1968(Castle et al, , 1972Gordon, 1973;Fales et al, 1995) in which milk production per hectare increased with increasing SR irrespective of the effect of SR on milk yield per cow. In fact, Castle et al (1972) reported that SR explained 92% of the variation in milk production per hectare. Irrespective of SR, there was no significant (P = 0.25) effect on the amount of milk produced per kilogram of feed consumed (0.9 kg of milk/kg of pasture + silage consumed).…”
Section: Milk Production Bw and Bcssupporting
confidence: 93%
“…Stocking rate (SR) is defined as the number of animals allocated to an area of land (i.e., cows/ha), and it has been recognized as the primary driver of milk production per hectare and profitability in grazing systems for over half a century (McMeekan, 1956;Castle et al, 1972). Extension of short-term studies investigating the effect of pasture allowance on DMI and pasture utilization indicates an increase in pasture utilization and a decrease in per cow production as SR increases (Castle et al, 1968;Gordon, 1973;Baker and Leaver, 1986;Kennedy et al, 2006), and this is consistent with full lactation studies (Dillon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…observed within these results emphasise the appropriateness of the techniques applied in this study. Castle et al (1972) reported that over 19 years, SR and milk yield per cow explained 85% of the variation in total milk production. The impact of a one cow/ha SR increase on milk production per ha within the current data set (20.1% and 19.6% for Type I and Type II experiments, respectively) is similar to the findings of Journet and Demarquilly (1979) when comparing raw mean effects on similar data.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors affecting milk yield of the grazing dairy cow include herbage mass (HM), pasture allowance (PA), grazing management, and supplementation (Combellas and Hodgson, 1979;Peyraud et al, 1996). Stocking rate is considered the primary driver of milk output per hectare and of profitability in grazing systems (Castle et al, 1972).…”
Section: Introductionmentioning
confidence: 99%